1976
DOI: 10.1530/acta.0.0830166
|View full text |Cite
|
Sign up to set email alerts
|

Rise in Dehydroepiandrosterone and Oestrogens During Clomiphene Administration in Normal Men

Abstract: Serum concentrations of LH, FSH and testosterone, and urinary excretion of individual 17-ketosteroids, oestrogenic substances and free cortisol was investigated in 12 normal men after a daily administration of 50 mg clomiphene citrate for 14 days. A significant increase in the serum concentrations of LH, FSH and testosterone was seen after 8 days with a further increase when measured a week later. The percentual increase in urinary excretion of oestrogens and dehydroepiandrosterone was of the same order as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
4
15
0
Order By: Relevance
“…The elevations of the serum concentrations of FSH and LH were significant for the entire Group 1 and in agreement with previous reports (Bardin et al 1967;Heller et al 1969;Kampmann et al 1976). It might therefore be as¬ sumed that corresponding increases in the serum concentrations of testosterone and the urinary excretion of oestrogen derivatives had occurred (Heller et al 1969;Kampmann et al 1976).…”
Section: Discussionsupporting
confidence: 93%
“…The elevations of the serum concentrations of FSH and LH were significant for the entire Group 1 and in agreement with previous reports (Bardin et al 1967;Heller et al 1969;Kampmann et al 1976). It might therefore be as¬ sumed that corresponding increases in the serum concentrations of testosterone and the urinary excretion of oestrogen derivatives had occurred (Heller et al 1969;Kampmann et al 1976).…”
Section: Discussionsupporting
confidence: 93%
“…As described previously (Kampmann et al 1976) FSH, LH and testosterone were measured by radioimmunoassay, fractionation of urinary 17-ketosteroids (A, E, D) was performed with gas liquid chromatography and total oestrogens measured by a spectrofluorometric method. No side-effects were recorded from the clomiphene administra¬ tion.…”
Section: Hormone Department Statens Seruminstitut Andmentioning
confidence: 99%
“…But a significant correlation existed between rises of FSH and rises of oestrogens. This confirms that one action of FSH is to stimulate production of testicular oestrogens which presumably takes place in the Sertoli cells.Recently we published that clomiphene besides its well-known stimulatory effect on serum FSH, LH and testosterone (T) increases urinary dehydroepiandroste¬ rone (D) and urinary oestrogens (Oe) in normal men (Kampmann et al 1976).In this paper we have correlated the clomiphene induced rises in the above mentioned hormones plus the urinary androgen metabolites androsterone + aetio¬ cholanolone (A + E). The purpose of the paper has been to elucidate how these hormones are inter-related at physiological levels in men.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Two studies reported a clomiphene-induced increase in plasma DHEA and DHEAS concentrations when administered for 15 days [91,92].…”
Section: Clomiphenementioning
confidence: 99%